Business Ethics from a Theological Perspective: Building a Business Based on Love and Justice - Defllins Ante (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2025)
This article examines the application of Christian business ethics, focusing on how theological principles guide ethical decision-making in the marketplace. As businesses prioritize profitability, many Christian leaders aim to integrate faith values into their operations to promote fairness, justice, and compassion. The study explores key theological concepts such as honesty, integrity, stewardship, love, and justice, and how these principles can be applied in real-world business practices. The purpose of the article is to offer a practical framework for Christian business leaders to integrate ethical principles into leadership, employee relations, and customer interactions. Through a review of theological teachings and Christian business literature, the article provides actionable insights for translating faith into business decisions. The findings suggest that businesses applying Christian ethics experience improved long-term outcomes, including stronger relationships with employees, customers, and stakeholders. By emphasizing values like integrity, fairness, and servant leadership, Christian business leaders foster a culture of trust and accountability. This article contributes to Christian business ethics by offering both theological and practical guidance. It encourages leaders to view their work as a way to serve others and honor God, while promoting social responsibility, ethical behavior, and sustainable practices that positively impact society.